Atopic dermatitis pediatric patients show high rates of nasal and intestinal colonization by methicillin-resistant Staphylococcus aureus and coagulase-negative staphylococci - Mariana Fernandes Augusto de Oliveira; Daiane Bitencourt Agne; Ludmila Sento Sé Bastos; Laura Maria Andrade de Oliveira; Simone Saintive; Ekaterini Simoes Goudouris; Evandro Alves do Prado; Henrique Fragoso dos Santos; Raphael da Silva Pereira; Fernanda Sampaio Cavalcante; Dennis de Carvalho Ferreira; Kátia Regina Netto dos Santos (BMC Microbiology, 2024)
Abstract Background Atopic dermatitis (AD) patients have high rates of colonization by Staphylococcus aureus, which has been associated with worsening of the disease. This study characterized Staphylococcus spp isolates recovered from nares and feces of pediatric patients with AD in relation to antimicrobial susceptibility, staphylococcal cassette chromosome mec (SCCmec) type, presence of pvl genes and clonality. Besides, gut bacterial community profiles were compared with those of children without AD. Results All 55 AD patients evaluated had colonization by Staphylococcus spp. Fifty-three (96.4%) patients had colonization in both clinical sites, whereas one patient each was not colonize in the nares or gut. Staphylococcus aureus was identified in the nostrils and feces of 45 (81.8%) and 39 (70.9%) patients, respectively. Methicillin-resistant Staphylococcus spp. isolates were found in 70.9% of the patients, and 24 (43.6%) had methicillin-resistant S. aureus (MRSA). S. aureus (55.6%) and S. epidermidis (26.5%) were the major species found. The prevalent lineages of S. aureus were USA800/SCCmecIV (47.6%) and USA1100/SCCmecIV (21.4%), and 61.9% of the evaluated patients had the same genotype in both sites. Additionally, gut bacterial profile of AD patients exhibits greater dissimilarity from the control group than it does among varying severities of AD. Conclusions High rates of nasal and intestinal colonization by S. aureus and methicillin-resistant staphylococci isolates were found in AD patients. Besides, gut bacterial profiles of AD patients were distinctly different from those of the control group, emphasizing the importance of monitoring S. aureus colonization and gut microbiome composition in AD patients.